E.T.A. Hoffmann and the Serapiontic principle : critique and creativity - Brown, H. M. (Hilda Meldrum) (Studies in German literature, linguistics, and culture., 2006)
Critics have long sought to elucidate the multilayered texts of E.T.A. Hoffmann by applying to them a particular set of theories and ideas that Hoffmann himself subsumed under the heading of the 'Serapiontic Principle.' This principle, which Hoffmann expounded in his collection of tales 'Die Serapionsbrüder, ' involves a complex intersection of the artist's faculties of imagination and perception. However, Hoffmann's mode of presenting his theory presents an unusual problem: rather than the usual form of an essay or treatise, he adopts a fictional framework, complete with a set of "characters"; this in turn sets up a number of perspectives on the theory itself. This combination of literary and theoretical elements presents a severe challenge to critics, and not surprisingly there has been little agreement about what the 'principle' actually entails or its wider relevance. With the principle as prime focus, this book provides detailed analysis of a broadly based selection of Hoffmann's texts, both theoretical and literary. It offers new perspectives on his narrative invention and the range of his theoretical interests, thus redefining his place at the forefront of German Romanticism. Hilda Meldrum Brown is professor of German at St Hilda's College, University of Oxford.